Analisis Dualitas Program Linier dalam Optimasi Biaya Produksi Minuman pada Warung Kopi - Nerli Khairani; Ellys Rebecca Simanjuntak; Maysi Puspita; Keisya Amelia Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Problems in beverage production in small businesses often occur due to limited raw materials, production time, and operational costs, so that an optimal production combination is needed to minimize costs. This study discusses the application of linear programming duality in optimizing beverage production costs at the